Are product innovation and flexible technology complements? - Jung, Astrid (online, 2001)
Abstract:
urn:nbn:de:0168-ssoar-115160
Keywords: (stw)1992-1994; (stw)Theorie der Unternehmung; (stw)Innovation; (stw)Flexibles Fertigungssystem; (stw)Monopol; (stw)Kostenfunktion; (stw)Fixkosten; (stw)Mathematische Optimierung; (stw)Theorie; (thesoz)Bundesrepublik Deutschland; (thesoz)Produkt; (thesoz)Kostenstruktur; (thesoz)Innovation; (thesoz)Nachfrageelastizität; (thesoz)Gewinn; (thesoz)Maschinenbau; (thesoz)gemischtwirtschaftliches Unternehmen; (thesoz)Kostensenkung; (thesoz)Technologie; (thesoz)Monopol; (thesoz)Modularisierung; (thesoz)Interdependenz; (thesoz)Informationstechnologie; (thesoz)Flexibilität; (thesoz)Produktionstechnik; Arbeitspapier; Graue Literatur; Buch; Unternehmenstheorie; Innovation; Flexible Fertigung; Bilaterales Monopol; Monopol; Kostenfunktion; Fixe Kosten; Optimierung; Theorie; :z Geschichte 1992-1994